2016
DOI: 10.1007/978-3-319-44902-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Do You Own a Volkswagen? Values as Non-Functional Requirements

Abstract: Abstract. Of late, there has been renewed interest in determining the role and relative importance of (moral) values in the design of software and its acceptance. Events such as the Snowden revelations and the more recent case of the Volkswagen "defeat device" software have further emphasised the importance of values and ethics in general. This paper posits a view that values accompanied by an appropriate framework derived from non-functional requirements can be used by designers and developers as means for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
10
0
4
Order By: Relevance
“…En la literatura también se emplean nombres de práctica como "documentación de requisitos no funcionales" [4], "especificación de requisitos no funcionales" [6], "gestión de conocimiento arquitectónico" [7], "evaluación de la calidad de los requisitos no funcionales" [8], "educción de requisitos no funcionales" [9] y "confianza en conocimiento tácito" [10]. En todos estos casos se tiene, efectivamente, un verbo nominalizado y un objeto, que puede ser un sustantivo ("conocimiento") o un sintagma nominal ("calidad de los requisitos").…”
Section: Antecedentesunclassified
See 3 more Smart Citations
“…En la literatura también se emplean nombres de práctica como "documentación de requisitos no funcionales" [4], "especificación de requisitos no funcionales" [6], "gestión de conocimiento arquitectónico" [7], "evaluación de la calidad de los requisitos no funcionales" [8], "educción de requisitos no funcionales" [9] y "confianza en conocimiento tácito" [10]. En todos estos casos se tiene, efectivamente, un verbo nominalizado y un objeto, que puede ser un sustantivo ("conocimiento") o un sintagma nominal ("calidad de los requisitos").…”
Section: Antecedentesunclassified
“…Barn [9] literalmente establece que la práctica "educción de requisitos no funcionales" se realiza "sistemáticamente", por lo cual el nombramiento de esa práctica se establece como "educción sistemática de requisitos no funcionales".…”
Section: Nombramiento De Las Prácticas Relacionadas Con Requisitounclassified
See 2 more Smart Citations
“…Barn [59], proposed that, in light of recent scandals like the Volkswagen-emissions scandal, values should be included in software development as a non-functional requirement. They suggested that "values accompanied by an appropriate framework derived from non-functional requirements" [p. 1] can be used by software engineers as a means for discussion of ethical issues of the design of software.…”
Section: Ethics In Ictmentioning
confidence: 99%